High-temperature-resistant and high-pressure-resistant sealing material as well as preparation method and application thereof
By using a mixing system of nitrile rubber and ethylene propylene rubber in the sealing material, and adding modifiers and reinforcement, the insufficient performance of existing sealing materials in high temperature and high pressure environments is solved, and the efficient sealing of materials is achieved and mechanical performance improvement.
Patent Information
- Application Number
- CN202411795599.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
AI Technical Summary
Existing sealing materials show poor sealing and mechanical properties in high temperature and high pressure environments, and poor compatibility between polar rubber and non-polar rubber affects the overall performance of the material.
Nitrile butadiene rubber and ethylene-propylene rubber are used as the main body of mixing. By adding modifiers such as carbon nanotube modifiers, the compatibility of the two is improved, and combined with reinforcement materials such as modified chitosan and alumina, the optimization of Functional properties of the material.
It has achieved good sealing performance and mechanical properties of sealing materials under high temperature and high pressure conditions, and has significantly improved its overall performance and is suitable for automotive sealing materials and other fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sealing material preparation, and in particular relates to a high temperature and high pressure resistant sealing material and a preparation method and application thereof. Background Art
[0002] Sealing materials are widely used in many industries such as machinery, automobiles, aerospace, construction and electronics. They are mainly used to prevent fluid leakage, block dust and foreign matter, reduce shock and sound insulation, etc. With the continuous development of industrialization and technology, the performance requirements for sealing materials are also increasing; modern sealing materials not only need to have good sealing, wear resistance and corrosion resistance, but also need to adapt to the challenges of high temperature, high pressure, chemical media and harsh environment. The sealing methods are divided into dynamic sealing and static sealing. Dynamic sealing refers to the sealing between parts that move relative to each other in the equipment, mainly referring to valve stem sealing. Dynamic sealing includes two basic forms: rotary sealing and reciprocating sealing; static sealing refers to two seals that are in a stationary state without relative movement.
[0003] The most widely used static sealing material is rubber sealing material, which is mainly based on rubber and uses the excellent properties of rubber to achieve the sealing effect, such as high elasticity, permeability resistance, chemical resistance and aging resistance of rubber. Because of its unique excellent elastic properties, rubber sealing materials can better provide pressure when in contact with equipment, and can fill the gaps in mechanical equipment as needed to achieve the purpose of sealing various equipment. In addition, there are many types of materials that can be used to make seals in rubber, and most rubber materials have a wide temperature range, which can better meet the different use conditions of seals. Secondly, when rubber materials are used as seals, due to their elasticity, they are very convenient to install and have strong designability, and are widely used in various industries. Therefore, rubber has occupied a dominant position in the materials used in the non-metallic sealing industry and plays an irreplaceable role in engineering operations.
[0004] The rubber used in rubber sealing materials can be divided into polar rubber and non-polar rubber, among which polar rubber includes nitrile rubber, fluororubber, etc., and non-polar rubber includes natural rubber, EPDM rubber, styrene-butadiene rubber, etc. Both have advantages and disadvantages. Polar rubber (such as nitrile rubber) has good oil resistance, wear resistance, and mechanical properties, but poor temperature resistance, poor ozone resistance, and insufficient elasticity; polar rubber has good high temperature resistance, elasticity, and ozone resistance, but poor oil resistance and wear resistance. Among them, among polar rubbers, nitrile rubber has the best oil resistance among general rubbers and is the most stable to chemicals. It has been used in many applications in practice. For example, patent document CN110628098A provides a high-temperature resistant nitrile sealing material and a preparation method thereof, comprising the following raw materials in parts by weight: 95-105 parts of nitrile rubber, 78-82 parts of filler, 8-9 parts of compounding agent, 1.8-2.2 parts of coumarone, 4.5-5.5 parts of zinc oxide, 1.4-1.6 parts of stearic acid, 2.4-2.6 parts of antioxidant, 5-6 parts of demoulding aid, 3-5 parts of accelerator, 0.7-0.9 parts of vulcanizing agent, and 0.3-0.5 parts of sulfur powder. The obtained sealing material can still be used as a sealing material at 130°C, but it does not overcome the defects of nitrile rubber itself.
[0005] For example, patent document CN101824172A provides a method for preparing a high temperature and high pressure resistant rubber sealing material, the preparation method comprising: firstly weighing 100 parts of hydrogenated nitrile rubber by weight and putting it into an open mill for plasticizing, and then adding 2-20 parts of metal oxide, 1-5 parts of stearic acid, 5-100 parts of acrylate, 10-70 parts of carbon black, 1-6 parts of antioxidant, 5-30 parts of plasticizer, 2-10 parts of anti-scorch agent, 2-10 parts of vulcanizing agent and 2-10 parts of vulcanizing aid. -10 parts, are added into an open mill in sequence for mixing until uniformly mixed, the mixed rubber is subjected to one-stage vulcanization in a flat vulcanizer, the vulcanization temperature is controlled to be 150-180°C, the vulcanization time is 20-40 minutes, and the vulcanization pressure is 10-20MPa. After the rubber is taken out from the flat vulcanizer, it is subjected to two-stage vulcanization at a temperature of 150-180°C. The obtained sealing material has good high temperature resistance, but the rubber used is hydrogenated nitrile rubber, which is still only a single polar rubber.
[0006] For another example, patent document CN107118408A provides an oil-resistant and chemically resistant sealing material for a chemical pump, which is made of the following ingredients by weight: 120-125 parts of nitrile rubber, 18-20 parts of EPDM rubber / polymethanol blend, 3.3-3.5 parts of modified sericite powder, 6-8 parts of epoxy resin, 1-3 parts of propylene alcohol, 2.5-2.8 parts of stearic acid, 1.6-1.9 parts of 4-nitrophthalate, 1.5-1.8 parts of carbon black, 1.0-1.3 parts of coupling agent, 1.2-1.6 parts of plasticizer, and 0.6-0.8 parts of vulcanizing agent. It uses nitrile rubber and EPDM rubber for mixing, and comprehensively utilizes the advantages of polar rubber and non-polar rubber. However, there is a disadvantage of poor compatibility when mixing polar rubber and non-polar rubber.
[0007] In view of the shortcomings of the prior art, the present invention hopes to provide a sealing material based on nitrile rubber compound. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high temperature and high pressure resistant sealing material and a preparation method and application thereof, taking nitrile rubber and ethylene propylene rubber as the main mixing body, adding a modifier to improve the compatibility of the two, optimizing the use of functional substances, so that the obtained sealing material has good sealing performance, high temperature and high pressure resistance, and excellent comprehensive performance.
[0009] In order to achieve the above object, the present invention adopts the following technical solution: In a first aspect, the present invention provides a high temperature and high pressure resistant sealing material, comprising the following raw materials: 65-85 parts of nitrile rubber, 15-35 parts of ethylene propylene rubber, 2-5 parts of a modifier, 30-50 parts of a reinforcing material, 5-12 parts of a plasticizer, 1-2.5 parts of a vulcanizing agent, 1-2.5 parts of a cross-linking aid, and 2-8 parts of an activator; Wherein, the preparation of the modifier comprises the following steps: S11, placing the carbon nanotubes in a mixed concentrated acid, heating them, and then washing and drying them to obtain pre-modified carbon nanotubes; S12, adding the pre-modified carbon nanotubes obtained in step S11 into ethanol, dispersing them evenly to obtain a dispersion; subsequently, adding α-hydroxy-ω-amino polyethylene glycol into the dispersion, followed by stirring, filtering, washing and drying to obtain a modifier.
[0010] As a preferred embodiment of the technical solution of the present invention, in step S11, the usage ratio of carbon nanotubes and mixed concentrated acid is 1 g: 5-10 mL; The mixed concentrated acid is prepared by mixing sulfuric acid and nitric acid in a volume ratio of 3:1; The heating treatment temperature is 120~140℃ and the treatment time is 10~30min.
[0011] As a preferred embodiment of the technical solution of the present invention, in step S12, the concentration of the dispersion is 0.5-2 mg / mL; the dosage ratio of the pre-modified carbon nanotubes and α-hydroxy-ω-amino polyethylene glycol is 1 g: 0.04-0.06 mol; The stirring treatment temperature is room temperature and the treatment time is 12~36h.
[0012] As a preferred embodiment of the technical solution of the present invention, the active agent is selected from one or more of zinc oxide, stearic acid, zinc stearate or calcium stearate; The plasticizer is selected from one or more of plasticizer TP-95, dioctyl phthalate, dioctyl sebacate or trioctyl trimellitate; The vulcanizing agent is selected from one or two of BIPB and sulfur; The auxiliary cross-linking agent is selected from one or two of TAC and TAIC.
[0013] As a preferred embodiment of the technical solution of the present invention, the preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a sodium hydroxide solution, treating it under heating conditions, then adding chloroacetic acid, and then treating it, filtering and drying it after the treatment is completed to obtain modified chitosan; S22, adding aluminum sulfate 18hydrate to water, stirring evenly, then adding ammonium fluoride and ethanolamine, followed by heating and stirring, after the treatment is completed, evaporating water, and then carbonizing and calcining to obtain pre-modified alumina; S23, placing the pre-modified alumina obtained in step S22 in a citric acid solution, dispersing it evenly, and then performing a heating treatment. After the treatment is completed, washing, drying, grinding, and screening are performed to obtain modified alumina; S24, adding the modified chitosan obtained in step S21 and the modified alumina obtained in step S23 into water respectively, treating them under heating conditions, and after the treatment, centrifuging, washing and drying to obtain a reinforcing material.
[0014] As a preferred embodiment of the technical solution of the present invention, in step S21, the usage ratio of chitosan, sodium hydroxide solution and chloroacetic acid is 1 g: 8-15 mL: 1.5-2.5 g; The concentration of sodium hydroxide solution is 15~25wt%; The heating temperature is 40~60℃, and the treatment time before adding chloroacetic acid is 0.5~3h; The treatment time after adding chloroacetic acid is 2~6h.
[0015] As a preferred embodiment of the technical solution of the present invention, in step S22, the mass ratio of aluminum sulfate 18hydrate, water, ammonium fluoride, and ethanolamine is 10:50-100:0.3-0.5:3-6; The heating and stirring treatment temperature is 50~70℃, and the treatment time is 2~6h; The carbonization temperature is 250~265℃ and the treatment time is 0.5~2h; The calcination temperature is 980~1000℃, and the calcination time is 1~4h.
[0016] As a preferred embodiment of the technical solution of the present invention, in step S23, the concentration of the citric acid solution is 0.1-0.2 mol / L; The mass ratio of pre-modified alumina to citric acid solution is 1:3~8; The heating treatment temperature is 30~40℃ and the treatment time is 2~6h; The mesh number of the grinding screen is 80~150 mesh.
[0017] As a preferred embodiment of the technical solution of the present invention, in step S24, the mass ratio of modified chitosan, modified alumina and water is 1:0.5-0.8:8-15; The heating temperature is 30~35℃ and the processing time is 2~6h.
[0018] In a second aspect, the present invention provides a method for preparing the above-mentioned high temperature and high pressure resistant sealing material, comprising the following steps: Add nitrile rubber and ethylene propylene rubber to an open mill for plasticizing, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent to the open mill for mixing until uniformly mixed to obtain a rubber mixture, and after standing for 24 hours, vulcanize the rubber mixture in a flat vulcanizer. After the vulcanization is completed, a high temperature and high pressure resistant sealing material is obtained; The vulcanization temperature is 170°C, the vulcanization pressure is 10MPa, and the vulcanization time is 8~15min.
[0019] Accordingly, the sealing material prepared based on the present invention can be widely used in the field of sealing materials, including but not limited to the application in automobile sealing materials, especially the application in automobile interior sealing strips.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a high temperature and high pressure resistant sealing material, which has good sealing performance, is resistant to high temperature and high pressure, combines the advantages of polar nitrile rubber and non-polar ethylene propylene rubber, and has good comprehensive performance.
[0021] The present invention provides a high temperature and high pressure resistant sealing material, which improves the compatibility of acrylonitrile rubber and ethylene propylene rubber by using a modifier, thereby improving the comprehensive performance of the sealing material, and preliminarily improving the reinforcement performance of the sealing material. Specifically, the modifier of the present invention is obtained by using carbon nanotubes as the main material and modified by mixed acid and α-hydroxy-ω-amino polyethylene glycol. The mixed acid modification of the carbon nanotubes can preliminarily introduce carboxyl and or hydroxyl groups, improve its dispersibility in rubber, and the modification of α-hydroxy-ω-amino polyethylene glycol can further enrich the number of groups; the carbon nanotubes with good dispersibility are interspersed between the acrylonitrile rubber and the ethylene propylene rubber, playing a "bridge" role; and the amino, hydroxyl, carboxyl and other groups contained in the modified carbon nanotubes can hydrogen bond with the nitrile group of the acrylonitrile rubber with a large amount of use, thereby enhancing the compatibility between the carbon nanotubes and the rubber, thereby improving the compatibility between the acrylonitrile rubber and the ethylene propylene rubber and between the rubber and the carbon nanotubes. At the same time, carbon nanotubes themselves are a reinforcing material with excellent performance, which is also the main reason why the present invention selects carbon nanotubes as the raw material of the modifier.
[0022] The present invention provides a high temperature and high pressure resistant sealing material, based on the preliminary reinforcement of carbon nanotubes, and further provides a reinforcing material with chitosan and alumina as raw materials. Specifically, chitosan is first carboxylated to improve its compatibility and activity, so as to facilitate the composite effect with modified alumina; alumina itself is a very good reinforcing particle. Based on the purpose of improving its dispersibility, the present invention first performs fluorine-doping modification on it, and while initially improving its dispersibility, the introduced fluorine is not only convenient for subsequent citric acid treatment, but also can form hydrogen bonds with modified chitosan, and can further improve the flame retardancy of the material; the fluorine-doped alumina is further treated with citric acid, and while removing impurities, carboxyl and hydroxyl groups can be introduced based on the action of citric acid, thereby further improving the subsequent composite effect with chitosan. The modified chitosan and modified alumina can not only improve their dispersibility in the rubber matrix, but also have rich groups that can react with the modifier in the form of hydrogen bonds, etc., to synergistically improve the reinforcement effect.
[0023] In summary, the present invention uses nitrile rubber and ethylene propylene rubber as main raw materials, and through the effect of modifiers and the use of reinforcing materials, the use of various substances is optimized, so that the prepared sealing material has good comprehensive performance and good application prospects. DETAILED DESCRIPTION
[0024] Embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0025] Unless otherwise specified, the chemical reagents and production equipment involved in the present invention are purchased from the market.
[0026] Among them, the nitrile rubber has the brand name JSR230S, from Japan's Jetsiya; the EPDM rubber has the brand name 6950, from Germany's Lanxess.
[0027] Chitosan with a deacetylation degree of about 85% was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0028] The brand of carbon nanotubes is CNT100, produced by Beijing Zhongke Jinyan Technology Co., Ltd.
[0029] α-Hydroxy-ω-aminopolyethylene glycol, Xi'an Qiyue Biotechnology Co., Ltd.
[0030] Among them, the concentration of concentrated sulfuric acid is 98wt%, and the concentration of nitric acid is 68%.
[0031] Plasticizer TP-95 was purchased from Shanghai Kaiyin Chemical Co., Ltd.; BIPB-40 was purchased from Dongguan Haojun Rubber & Plastic Co., Ltd.; TAIC was purchased from Dalian Tianyuanji Chemical Co., Ltd.
[0032] At the same time, it should be noted that the parts mentioned in the present invention are all parts by weight unless otherwise specified. The processing processes mentioned, such as open refining, open mixing mill, flat plate vulcanizer, etc., are all mature processes or equipment, which are not described in detail in the present invention and are subject to the implementation of those skilled in the art.
[0033] Example 1
[0034] A high temperature and high pressure resistant sealing material is prepared from the following raw materials: 75g of nitrile rubber, 25g of ethylene propylene rubber, 3g of a modifier, 45g of a reinforcing material, 7.5g of a plasticizer (TP-95), 4g of zinc oxide, 2g of a vulcanizing agent (BIPB-40), 1.8g of a cross-linking agent (TAIC), and 1.5g of an activator (zinc stearate); Wherein, the preparation of the modifier comprises the following steps: S11, placing the carbon nanotubes in a mixed concentrated acid (sulfuric acid and nitric acid in a volume ratio of 3:1) at a dosage of 1 g:10 mL, heating (135° C., 12 min), and then washing and drying to obtain pre-modified carbon nanotubes; S12. Add the pre-modified carbon nanotubes obtained in step S11 into ethanol and disperse them evenly to obtain a dispersion (0.1 mg / mL); then, add α-hydroxy-ω-amino polyethylene glycol to the dispersion, and then stir it (room temperature, 18 h), filter it, wash it, and dry it to obtain a modifier; wherein the amount ratio of the pre-modified carbon nanotubes to the α-hydroxy-ω-amino polyethylene glycol is 1 g:0.05 mol.
[0035] Wherein, the preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a 20wt% sodium hydroxide solution, treating under heating conditions (50°C, 1h), then adding chloroacetic acid, and then treating (50°C, 4h), filtering and drying after the treatment to obtain modified chitosan; wherein the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid is 1g:10 mL:1.6g; S22, adding aluminum sulfate 18hydrate to water, stirring evenly, then adding ammonium fluoride and ethanolamine, and then heating and stirring (55°C, 3.5h), after the treatment is completed, evaporating water, and then carbonizing (260°C, 0.5h), calcining (1000°C, 1.5h) to obtain pre-modified alumina; wherein the mass ratio of aluminum sulfate 18hydrate, water, ammonium fluoride, and ethanolamine is 10:65:0.4:5; S23, placing the pre-modified alumina obtained in step S22 in a 0.15 mol / L citric acid solution at a mass ratio of 1:5, dispersing it evenly and then heating it (35°C, 3.5h). After the treatment is completed, washing, drying, grinding and sieving through 100 mesh to obtain modified alumina; S24. Add the modified chitosan obtained in step S21 and the modified alumina obtained in step S23 into water respectively, and treat them under heating conditions (30°C, 4h). After the treatment, centrifuge, wash and dry to obtain a reinforcing material; wherein the mass ratio of modified chitosan, modified alumina and water is 1:0.65:12.
[0036] In this embodiment, a method for preparing the above-mentioned high temperature and high pressure resistant sealing material is also provided, comprising the following steps: Add nitrile rubber and EPDM rubber into an open mill for plasticization, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent into the open mill for mixing until uniformly mixed to obtain a rubber mixture. After standing for 24 hours, the rubber mixture is vulcanized in a flat vulcanizer (170°C, 10MPa, 10min). After vulcanization, a high temperature and high pressure resistant sealing material is obtained.
[0037] Example 2
[0038] A high temperature and high pressure resistant sealing material is prepared from the following raw materials: 75g of nitrile rubber, 25g of ethylene propylene rubber, 2.8g of a modifier, 47g of a reinforcing material, 7.2g of a plasticizer (TP-95), 4.5g of zinc oxide, 2.2g of a vulcanizing agent (BIPB-40), 1.8g of a cross-linking agent (TAIC), and 1.3g of an activator (zinc stearate); Wherein, the preparation of the modifier comprises the following steps: S11, placing the carbon nanotubes in a mixed concentrated acid (sulfuric acid and nitric acid in a volume ratio of 3:1) at a dosage of 1 g:9 mL, heating (135°C, 10 min), and then washing and drying to obtain pre-modified carbon nanotubes; S12. Add the pre-modified carbon nanotubes obtained in step S11 into ethanol and disperse them evenly to obtain a dispersion (0.1 mg / mL); then, add α-hydroxy-ω-amino polyethylene glycol to the dispersion, and then stir it (room temperature, 24 h), filter it, wash it, and dry it to obtain a modifier; wherein the amount ratio of the pre-modified carbon nanotubes to the α-hydroxy-ω-amino polyethylene glycol is 1 g:0.055 mol.
[0039] Wherein, the preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a 20wt% sodium hydroxide solution, treating under heating conditions (50°C, 1.5h), then adding chloroacetic acid, and then treating (50°C, 3.5h), filtering and drying after the treatment to obtain modified chitosan; wherein the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid is 1g:10 mL:1.6g; S22, adding aluminum sulfate 18hydrate to water, stirring evenly, then adding ammonium fluoride and ethanolamine, and then heating and stirring (55°C, 4h), after the treatment is completed, evaporating water, and then carbonizing (260°C, 0.5h), calcining (1000°C, 1.5h) to obtain pre-modified alumina; wherein the mass ratio of aluminum sulfate 18hydrate, water, ammonium fluoride, and ethanolamine is 10:65:0.42:5.5; S23, placing the pre-modified alumina obtained in step S22 in a 0.15 mol / L citric acid solution at a mass ratio of 1:5, dispersing it evenly and then heating it (35°C, 4h). After the treatment, washing, drying, grinding and sieving through 100 mesh to obtain modified alumina; S24. Add the modified chitosan obtained in step S21 and the modified alumina obtained in step S23 into water respectively, and treat them under heating conditions (30°C, 3.5h). After the treatment, centrifuge, wash and dry to obtain a reinforcing material; wherein the mass ratio of modified chitosan, modified alumina and water is 1:0.65:12.
[0040] In this embodiment, a method for preparing the above-mentioned high temperature and high pressure resistant sealing material is also provided, comprising the following steps: Add nitrile rubber and EPDM rubber into an open mill for plasticization, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent into the open mill for mixing until uniformly mixed to obtain a rubber mixture. After standing for 24 hours, the rubber mixture is vulcanized in a flat vulcanizer (170°C, 10MPa, 10min). After vulcanization, a high temperature and high pressure resistant sealing material is obtained.
[0041] Example 3
[0042] A high temperature and high pressure resistant sealing material is prepared from the following raw materials: 75g of nitrile rubber, 25g of ethylene propylene rubber, 3.2g of a modifier, 43g of a reinforcing material, 8g of a plasticizer (TP-95), 3.8g of zinc oxide, 2.2g of a vulcanizing agent (BIPB-40), 2g of a cross-linking agent (TAIC), and 1.7g of an active agent (zinc stearate); Wherein, the preparation of the modifier comprises the following steps: S11, placing the carbon nanotubes in a mixed concentrated acid (sulfuric acid and nitric acid in a volume ratio of 3:1) at a dosage of 1 g:9 mL, heating (130°C, 12 min), and then washing and drying to obtain pre-modified carbon nanotubes; S12. Add the pre-modified carbon nanotubes obtained in step S11 into ethanol and disperse them evenly to obtain a dispersion (0.1 mg / mL); then, add α-hydroxy-ω-amino polyethylene glycol to the dispersion, and then stir it (room temperature, 20 h), filter it, wash it, and dry it to obtain a modifier; wherein the amount ratio of the pre-modified carbon nanotubes to the α-hydroxy-ω-amino polyethylene glycol is 1 g:0.05 mol.
[0043] Wherein, the preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a 20wt% sodium hydroxide solution, treating under heating conditions (50°C, 1.5h), then adding chloroacetic acid, and then treating (50°C, 4.5h), filtering and drying after the treatment, to obtain modified chitosan; wherein the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid is 1g:10 mL:1.5g; S22, adding aluminum sulfate 18hydrate to water, stirring evenly, then adding ammonium fluoride and ethanolamine, and then heating and stirring (55°C, 3.5h), after the treatment is completed, evaporating water, and then carbonizing (260°C, 0.5h) and calcining (1000°C, 1h) to obtain pre-modified alumina; wherein the mass ratio of aluminum sulfate 18hydrate, water, ammonium fluoride, and ethanolamine is 10:65:0.4:5; S23, placing the pre-modified alumina obtained in step S22 in a 0.15 mol / L citric acid solution at a mass ratio of 1:5, dispersing it evenly and then heating it (35°C, 4.5h). After the treatment is completed, washing, drying, grinding and sieving through 100 mesh to obtain modified alumina; S24. Add the modified chitosan obtained in step S21 and the modified alumina obtained in step S23 into water respectively, and treat them under heating conditions (30°C, 4.5h). After the treatment, centrifuge, wash and dry to obtain a reinforcing material; wherein the mass ratio of modified chitosan, modified alumina and water is 1:0.65:12.
[0044] In this embodiment, a method for preparing the above-mentioned high temperature and high pressure resistant sealing material is also provided, comprising the following steps: Add nitrile rubber and EPDM rubber into an open mill for plasticization, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent into the open mill for mixing until uniformly mixed to obtain a rubber mixture. After standing for 24 hours, the rubber mixture is vulcanized in a flat vulcanizer (170°C, 10MPa, 10min). After vulcanization, a high temperature and high pressure resistant sealing material is obtained.
[0045] Comparative Example 1
[0046] Compared with Example 1, the preparation of the modifier in Comparative Example 1 omits step S11. Specifically, this Comparative Example 1 provides a high temperature and high pressure resistant sealing material, which is prepared from the following raw materials: 75g of nitrile rubber, 25g of ethylene propylene rubber, 3g of modifier, 45g of reinforcing material, 7.5g of plasticizer (TP-95), 4g of zinc oxide, 2g of vulcanizing agent (BIPB-40), 1.8g of cross-linking agent (TAIC), and 1.5g of activator (zinc stearate); Wherein, the preparation of the modifier comprises the following steps: S11. Add carbon nanotubes into ethanol and disperse them evenly to obtain a dispersion (0.1 mg / mL). Subsequently, add α-hydroxy-ω-amino polyethylene glycol to the dispersion, followed by stirring (room temperature, 18 h), filtering, washing, and drying to obtain a modifier. The amount ratio of carbon nanotubes to α-hydroxy-ω-amino polyethylene glycol is 1 g:0.05 mol.
[0047] Wherein, the preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a 20wt% sodium hydroxide solution, treating under heating conditions (50°C, 1h), then adding chloroacetic acid, and then treating (50°C, 4h), filtering and drying after the treatment to obtain modified chitosan; wherein the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid is 1g:10 mL:1.6g; S22, adding aluminum sulfate 18hydrate to water, stirring evenly, then adding ammonium fluoride and ethanolamine, and then heating and stirring (55°C, 3.5h), after the treatment is completed, evaporating water, and then carbonizing (260°C, 0.5h), calcining (1000°C, 1.5h) to obtain pre-modified alumina; wherein the mass ratio of aluminum sulfate 18hydrate, water, ammonium fluoride, and ethanolamine is 10:65:0.4:5; S23, placing the pre-modified alumina obtained in step S22 in a 0.15 mol / L citric acid solution at a mass ratio of 1:5, dispersing it evenly and then heating it (35°C, 3.5h). After the treatment is completed, washing, drying, grinding and sieving through 100 mesh to obtain modified alumina; S24. Add the modified chitosan obtained in step S21 and the modified alumina obtained in step S23 into water respectively, and treat them under heating conditions (30°C, 4h). After the treatment, centrifuge, wash and dry to obtain a reinforcing material; wherein the mass ratio of modified chitosan, modified alumina and water is 1:0.65:12.
[0048] In this comparative example, a method for preparing the above-mentioned high temperature and high pressure resistant sealing material is also provided, comprising the following steps: Add nitrile rubber and EPDM rubber into an open mill for plasticization, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent into the open mill for mixing until uniformly mixed to obtain a rubber mixture. After standing for 24 hours, the rubber mixture is vulcanized in a flat vulcanizer (170°C, 10MPa, 10min). After vulcanization, a high temperature and high pressure resistant sealing material is obtained.
[0049] Comparative Example 2
[0050] Compared with Example 1, step S12 is omitted in the preparation of the modifier in Comparative Example 2. Specifically, this Comparative Example 2 provides a high temperature and high pressure resistant sealing material, which is prepared from the following raw materials: 75g of nitrile rubber, 25g of ethylene propylene rubber, 3g of modifier, 45g of reinforcing material, 7.5g of plasticizer (TP-95), 4g of zinc oxide, 2g of vulcanizing agent (BIPB-40), 1.8g of cross-linking agent (TAIC), and 1.5g of activator (zinc stearate); Wherein, the preparation of the modifier comprises the following steps: S11. Place the carbon nanotubes in a mixed concentrated acid (sulfuric acid and nitric acid in a volume ratio of 3:1) at a dosage of 1 g:10 mL, heat treat (135°C, 12 min), and then wash and dry to obtain a modifier.
[0051] Wherein, the preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a 20wt% sodium hydroxide solution, treating under heating conditions (50°C, 1h), then adding chloroacetic acid, and then treating (50°C, 4h), filtering and drying after the treatment to obtain modified chitosan; wherein the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid is 1g:10 mL:1.6g; S22, adding aluminum sulfate 18hydrate to water, stirring evenly, then adding ammonium fluoride and ethanolamine, and then heating and stirring (55°C, 3.5h), after the treatment is completed, evaporating water, and then carbonizing (260°C, 0.5h), calcining (1000°C, 1.5h) to obtain pre-modified alumina; wherein the mass ratio of aluminum sulfate 18hydrate, water, ammonium fluoride, and ethanolamine is 10:65:0.4:5; S23, placing the pre-modified alumina obtained in step S22 in a 0.15 mol / L citric acid solution at a mass ratio of 1:5, dispersing it evenly and then heating it (35°C, 3.5h). After the treatment is completed, washing, drying, grinding and sieving through 100 mesh to obtain modified alumina; S24. Add the modified chitosan obtained in step S21 and the modified alumina obtained in step S23 into water respectively, and treat them under heating conditions (30°C, 4h). After the treatment, centrifuge, wash and dry to obtain a reinforcing material; wherein the mass ratio of modified chitosan, modified alumina and water is 1:0.65:12.
[0052] In this comparative example, a method for preparing the above-mentioned high temperature and high pressure resistant sealing material is also provided, comprising the following steps: Add nitrile rubber and EPDM rubber into an open mill for plasticization, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent into the open mill for mixing until uniformly mixed to obtain a rubber mixture. After standing for 24 hours, the rubber mixture is vulcanized in a flat vulcanizer (170°C, 10MPa, 10min). After vulcanization, a high temperature and high pressure resistant sealing material is obtained.
[0053] Comparative Example 3
[0054] Compared with Example 1, the preparation step S22 of the reinforcing material in Comparative Example 3 is adjusted (without fluorine doping). Specifically, this Comparative Example 3 provides a high temperature and high pressure resistant sealing material, which is prepared from the following raw materials: 75g of nitrile rubber, 25g of ethylene propylene rubber, 3g of modifier, 45g of reinforcing material, 7.5g of plasticizer (TP-95), 4g of zinc oxide, 2g of vulcanizing agent (BIPB-40), 1.8g of cross-linking agent (TAIC), and 1.5g of activator (zinc stearate); Wherein, the preparation of the modifier comprises the following steps: S11, placing the carbon nanotubes in a mixed concentrated acid (sulfuric acid and nitric acid in a volume ratio of 3:1) at a dosage of 1 g:10 mL, heating (135° C., 12 min), and then washing and drying to obtain pre-modified carbon nanotubes; S12. Add the pre-modified carbon nanotubes obtained in step S11 into ethanol and disperse them evenly to obtain a dispersion (0.1 mg / mL); then, add α-hydroxy-ω-amino polyethylene glycol to the dispersion, and then stir it (room temperature, 18 h), filter it, wash it, and dry it to obtain a modifier; wherein the amount ratio of the pre-modified carbon nanotubes to the α-hydroxy-ω-amino polyethylene glycol is 1 g:0.05 mol.
[0055] Wherein, the preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a 20wt% sodium hydroxide solution, treating under heating conditions (50°C, 1h), then adding chloroacetic acid, and then treating (50°C, 4h), filtering and drying after the treatment to obtain modified chitosan; wherein the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid is 1g:10 mL:1.6g; S22, adding aluminum sulfate 18hydrate to water, stirring evenly and then adding ethanolamine, followed by heating and stirring treatment (55°C, 3.5h), after the treatment is completed, evaporating water, and then carbonizing (260°C, 0.5h) and calcining (1000°C, 1.5h) to obtain pre-modified alumina; wherein the mass ratio of aluminum sulfate 18hydrate, water, and ethanolamine is 10:65:5; S23, placing the pre-modified alumina obtained in step S22 in a 0.15 mol / L citric acid solution at a mass ratio of 1:5, dispersing it evenly and then heating it (35°C, 3.5h). After the treatment is completed, washing, drying, grinding and sieving through 100 mesh to obtain modified alumina; S24. Add the modified chitosan obtained in step S21 and the modified alumina obtained in step S23 into water respectively, and treat them under heating conditions (30°C, 4h). After the treatment, centrifuge, wash and dry to obtain a reinforcing material; wherein the mass ratio of modified chitosan, modified alumina and water is 1:0.65:12.
[0056] In this comparative example, a method for preparing the above-mentioned high temperature and high pressure resistant sealing material is also provided, comprising the following steps: Add nitrile rubber and EPDM rubber into an open mill for plasticization, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent into the open mill for mixing until uniformly mixed to obtain a rubber mixture. After standing for 24 hours, the rubber mixture is vulcanized in a flat vulcanizer (170°C, 10MPa, 10min). After vulcanization, a high temperature and high pressure resistant sealing material is obtained.
[0057] Comparative Example 4
[0058] Compared with Example 1, step S23 is omitted in the preparation of the reinforcing material in Comparative Example 4. Specifically, this Comparative Example 4 provides a high temperature and high pressure resistant sealing material, which is prepared from the following raw materials: 75g of nitrile rubber, 25g of ethylene propylene rubber, 3g of modifier, 45g of reinforcing material, 7.5g of plasticizer (TP-95), 4g of zinc oxide, 2g of vulcanizing agent (BIPB-40), 1.8g of cross-linking agent (TAIC), and 1.5g of activator (zinc stearate); Wherein, the preparation of the modifier comprises the following steps: S11, placing the carbon nanotubes in a mixed concentrated acid (sulfuric acid and nitric acid in a volume ratio of 3:1) at a dosage of 1 g:10 mL, heating (135° C., 12 min), and then washing and drying to obtain pre-modified carbon nanotubes; S12. Add the pre-modified carbon nanotubes obtained in step S11 into ethanol and disperse them evenly to obtain a dispersion (0.1 mg / mL); then, add α-hydroxy-ω-amino polyethylene glycol to the dispersion, and then stir it (room temperature, 18 h), filter it, wash it, and dry it to obtain a modifier; wherein the amount ratio of the pre-modified carbon nanotubes to the α-hydroxy-ω-amino polyethylene glycol is 1 g:0.05 mol.
[0059] Wherein, the preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a 20wt% sodium hydroxide solution, treating under heating conditions (50°C, 1h), then adding chloroacetic acid, and then treating (50°C, 4h), filtering and drying after the treatment to obtain modified chitosan; wherein the amount ratio of chitosan, sodium hydroxide solution, and chloroacetic acid is 1g:10 mL:1.6g; S22, adding aluminum sulfate 18hydrate to water, stirring evenly, then adding ammonium fluoride and ethanolamine, and then heating and stirring (55°C, 3.5h), after the treatment is completed, evaporating water, and then carbonizing (260°C, 0.5h), calcining (1000°C, 1.5h) to obtain modified alumina; wherein the mass ratio of aluminum sulfate 18hydrate, water, ammonium fluoride, and ethanolamine is 10:65:0.4:5; S23. Add the modified chitosan obtained in step S21 and the modified alumina obtained in step S22 into water respectively, treat them under heating conditions (30°C, 4h), and after the treatment, centrifuge, wash and dry them to obtain a reinforcing material; wherein the mass ratio of modified chitosan, modified alumina and water is 1:0.65:12.
[0060] In this comparative example, a method for preparing the above-mentioned high temperature and high pressure resistant sealing material is also provided, comprising the following steps: Add nitrile rubber and EPDM rubber into an open mill for plasticization, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent into the open mill for mixing until uniformly mixed to obtain a rubber mixture. After standing for 24 hours, the rubber mixture is vulcanized in a flat vulcanizer (170°C, 10MPa, 10min). After vulcanization, a high temperature and high pressure resistant sealing material is obtained.
[0061] The sealing materials prepared in Example 1 and Comparative Examples 1 to 4 were tested for performance as follows: The tensile strength is measured in accordance with GB / T 528-2009; The tear strength is measured in accordance with GB / T 529-2008; The resilience performance is carried out according to GB / T 20671.2 Procedure A; The compression resistance test is carried out according to GB / T 22307-2008, at a temperature of 150°C; The high temperature and high pressure resistance test is carried out in accordance with GB / T 540-2008; The sealing performance test was carried out according to GB / T 12385-2008 test method B. The obtained sealing material was processed into a wound non-metallic gasket. The sealing medium was nitrogen, the pressure was 5.5MPa, the compression stress was 70MPa, and the leakage rate was calculated. The test results are shown in Table 1.
[0062] Table 1 Test results
[0063] It can be seen from Table 1 that the sealing material prepared by the present invention is resistant to high temperature and high pressure, and has good mechanical properties and good sealing performance.
[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high temperature and high pressure resistant sealing material, characterized in that: The preparation raw materials include: 65-85 parts of nitrile rubber, 15-35 parts of ethylene-propylene rubber, 2-5 parts of modifier, 30-50 parts of reinforcing material, 5-12 parts of plasticizer, 1-2.5 parts of vulcanizing agent, 1-2.5 parts of auxiliary cross-linking agent, and 2-8 parts of activator; Wherein, the preparation of the modifier comprises the following steps: S11, placing the carbon nanotubes in a mixed concentrated acid, heating them, and then washing and drying them to obtain pre-modified carbon nanotubes; S12, adding the pre-modified carbon nanotubes obtained in step S11 into ethanol, dispersing them evenly to obtain a dispersion; subsequently, adding α-hydroxy-ω-amino polyethylene glycol into the dispersion, followed by stirring, filtering, washing and drying to obtain a modifier.
2. A high temperature and high pressure resistant sealing material according to claim 1, characterized in that: In step S11, the ratio of carbon nanotubes to mixed concentrated acid is 1 g: 5-10 mL; The mixed concentrated acid is prepared by mixing sulfuric acid and nitric acid in a volume ratio of 3:1; The heating treatment temperature is 120~140℃ and the treatment time is 10~30min; In step S12, the concentration of the dispersion is 0.5-2 mg / mL; The dosage ratio of pre-modified carbon nanotubes and α-hydroxy-ω-amino polyethylene glycol is 1 g: 0.04-0.06 mol; The stirring treatment temperature is room temperature and the treatment time is 12~36h.
3. The high temperature and high pressure resistant sealing material according to claim 1, characterized in that: The active agent is selected from one or more of zinc oxide, stearic acid, zinc stearate or calcium stearate; The plasticizer is selected from one or more of plasticizer TP-95, dioctyl phthalate, dioctyl sebacate or trioctyl trimellitate; The vulcanizing agent is selected from one or two of BIPB and sulfur; The auxiliary cross-linking agent is selected from one or two of TAC and TAIC.
4. The high temperature and high pressure resistant sealing material according to claim 1, characterized in that: The preparation of the reinforcing material comprises the following steps: S21, adding chitosan to a sodium hydroxide solution, treating it under heating conditions, then adding chloroacetic acid, and then treating it, filtering and drying it after the treatment is completed to obtain modified chitosan; S22, adding aluminum sulfate 18hydrate to water, stirring evenly, then adding ammonium fluoride and ethanolamine, followed by heating and stirring, after the treatment is completed, evaporating water, and then carbonizing and calcining to obtain pre-modified alumina; S23, placing the pre-modified alumina obtained in step S22 in a citric acid solution, dispersing it evenly, and then performing a heating treatment. After the treatment is completed, washing, drying, grinding, and screening are performed to obtain modified alumina; S24, adding the modified chitosan obtained in step S21 and the modified alumina obtained in step S23 into water respectively, treating them under heating conditions, and after the treatment, centrifuging, washing and drying to obtain a reinforcing material.
5. A high temperature and high pressure resistant sealing material according to claim 4, characterized in that: In step S21, the ratio of chitosan, sodium hydroxide solution and chloroacetic acid is 1 g: 8-15 mL: 1.5-2.5 g; The concentration of sodium hydroxide solution is 15~25wt%; The heating temperature is 40~60℃, and the treatment time before adding chloroacetic acid is 0.5~3h; The treatment time after adding chloroacetic acid is 2~6h.
6. The high temperature and high pressure resistant sealing material according to claim 4, characterized in that: In step S22, the mass ratio of aluminum sulfate 18hydrate, water, ammonium fluoride, and ethanolamine is 10:50-100:0.3-0.5:3-6; The heating and stirring treatment temperature is 50~70℃, and the treatment time is 2~6h; The carbonization temperature is 250~265℃ and the treatment time is 0.5~2h; The calcination temperature is 980~1000℃, and the calcination time is 1~4h.
7. The high temperature and high pressure resistant sealing material according to claim 4, characterized in that: In step S23, the concentration of the citric acid solution is 0.1-0.2 mol / L; The mass ratio of pre-modified alumina to citric acid solution is 1:3~8; The heating treatment temperature is 30~40℃ and the treatment time is 2~6h; The mesh number of the grinding screen is 80~150 mesh.
8. The high temperature and high pressure resistant sealing material according to claim 4, characterized in that: In step S24, the mass ratio of modified chitosan, modified alumina, and water is 1:0.5-0.8:8-15; The heating temperature is 30~35℃ and the processing time is 2~6h.
9. A method for preparing the high temperature and high pressure resistant sealing material according to any one of claims 1 to 8, characterized in that: The steps include: Add nitrile rubber and ethylene propylene rubber to an open mill for plasticizing, then add modifier, reinforcing material, activator, plasticizer, vulcanizer and cross-linking agent to the open mill for mixing until uniformly mixed to obtain a rubber mixture, and after standing for 24 hours, vulcanize the rubber mixture in a flat vulcanizer. After the vulcanization is completed, a high temperature and high pressure resistant sealing material is obtained; The vulcanization temperature is 170°C, the vulcanization pressure is 10MPa, and the vulcanization time is 8~15min.
10. Use of the high temperature and high pressure resistant sealing material according to any one of claims 1 to 8 in the preparation of automobile sealing strips.
Citation Information
Patent Citations
Preparation method of high temperature and high pressure resistant rubber sealing material
CN101824172A
Oil-resisting and chemical-resisting sealing material for chemical pump
CN107118408A
High-temperature-resistant butyronitrile sealing material and preparation method thereof
CN110628098A